Rich-colour mechanochromism of a cyanostilbene derivative with chiral self-assembly. (14th June 2021) - Wen, Li; Sun, Jingwei; Li, Chengjian; Zhu, Chenfei; Zhang, Xi; Wang, Zhenbo; Song, Qingbao; Lv, Chunyan; Zhang, Yujian
Abstract : The tricolored fluorescence switching was realized in a novel chiral fluorophore. The fabrication of a helical assembly was proposed as a candidate strategy for attaining an additional metastable state, which contributed to enriched PL colors via pairwise excimer emission. Abstract : Mechanochromic luminophores exhibiting rich-colour transitions among multiple states have important potential applications, but few such compounds are known. Herein, chiral self-assembly fabrication is proposed as a valid method to realize a new type of metastable state, which may bring enriched PL colours. A novel chiral fluorophore, ACNS, was synthesized and assembled into helices with specific handedness, showing a tricolour photoluminescence (PL) transition among yellow, green and blue under grinding and other stimuli. The crystalline ACNS powder (B-phase) emits bright sky-blue light. Interestingly, the luminophore assembles into helical nanofibres (Y-phase) with specific handedness, which present yellow fluorescence at 539 nm. Moreover, upon grinding, both Y-phase and B-phase powder change into green-emitting powder (G-Phase) with a PL peak at 498 nm. This strategy is conceptually simple and affords a promising approach to the development of mechanochromic luminophores with multicolour fluorescence switching.